To be or not to be manipulated by our bacteria? - LE BORGNE, Marc; Le Borgne, Marina; Sossou-Echavidre, Kézia; Janssen, Christine (De Remediis, 2024)
The gut microbiota has become a central focus of research since its intricate connection with the brain was identified. Notably, the gut microbiota can influence mental health, opening new prospects for improving the management of psychiatric disorders. Understanding the bidirectional interactions between the brain, gut, and microbiome is crucial for evaluating the true impact of gut microbiota on mental health and its subsequent implications for psychiatry. Currently, the brain-gut-microbiome axis communicates through five interconnected pathways: the immune system, the vagus nerve, the enteric nervous system, the neuroendocrine system, and the circulatory system. The development of microbiota-based therapeutics signals significant changes in current clinical practices. Furthermore, microbiome-based therapeutics are expected to undergo substantial regulatory transformations in Europe in the coming years. This mini-review aims to explore these aspects to evaluate the potential of gut bacteria to shape mental health interventions.